2010
DOI: 10.1177/0265532209349472
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the decision-making process of standard setting participants

Abstract: Despite the growing interest of the language testing community in standard setting, primarily due to the use of the Common European Framework of Reference (CEFR-Council of Europe, 2001), the participants’ decision-making process in the CEFR standard setting context remains unexplored. This study attempts to fill in this gap by analyzing these participants’ group discussions during a CEFR standard setting research project. Using an inductively and deductively-built analytical framework, it was found that decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 23 publications
0
18
0
2
Order By: Relevance
“…However, overall band levels and overall performance descriptors might be useful for score users who need a holistic evaluation of language ability. Moreover, because external criteria such as the CEFR scales are intentionally context-free so that they can have a wide range of applications, researchers note problems when using them in specific contexts, such as the design of test specifications (Alderson et al, 2006) or the setting of cut scores (Papageorgiou, 2010a). It has also been pointed out that external proficiency scales, such as the ones from the CEFR, are intentionally underspecified and their level of abstraction is too high, resulting in a gap between the score and its meaning (Fulcher et al, 2011, p. 8).…”
Section: Developing and Validating Band Levels And Descriptors For Rementioning
confidence: 99%
“…However, overall band levels and overall performance descriptors might be useful for score users who need a holistic evaluation of language ability. Moreover, because external criteria such as the CEFR scales are intentionally context-free so that they can have a wide range of applications, researchers note problems when using them in specific contexts, such as the design of test specifications (Alderson et al, 2006) or the setting of cut scores (Papageorgiou, 2010a). It has also been pointed out that external proficiency scales, such as the ones from the CEFR, are intentionally underspecified and their level of abstraction is too high, resulting in a gap between the score and its meaning (Fulcher et al, 2011, p. 8).…”
Section: Developing and Validating Band Levels And Descriptors For Rementioning
confidence: 99%
“…A qualitative approach to investigating the judges' decision-making process when setting cut scores to the CEFR was employed by Papageorgiou (2010a). The study investigated the factors reportedly affecting the panelists' decision to set a cut score and the problems faced when setting cut scores in relation to the CEFR.…”
Section: Exploring the Quality Of Alignment With The Cefrmentioning
confidence: 99%
“…Papageorgiou (2010), for example, identified problems with the CEFR descriptors when used for setting cut scores. Participants of his standard-setting study reported that the context-free characteristics of the framework made it less applicable to a language testing context.…”
Section: Issues With the Cefrmentioning
confidence: 99%